The role played by recruitment agencies in the emigration of South African nurses - Oosthuizen, M J; Ehlers, V J; Jooste, K (Health SA = SA Gesondheid, 2005)
Active recruitment of foreign nurses might offer solutions to many countries’ nursing shortages. Opsomming Die aktiewe werwing van buitelandse verpleegkundiges kan oplossings bied vir baie lande se tekorte aan verpleegkundiges. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.